Two new Trophoninae (Gastropoda: Muricidae) from Antarctic waters - Pastorino, Roberto Santiago Guido
Two new species of Trophon from Antarctic waters are described. Trophon emilyae, n. sp., from the northwestern Amundsen Sea, is characterized by a small, slender, almost smooth shell and a thin profile. Axial sculpture consists of regular, thin varices, and four weak cords on the first whorls are the only spiral ornamentation. It is similar to T. declinans Watson, 1882, but the radula and shell ornamentation are clearly different. Trophon arnaudi, n. sp., was collected off South Sandwich Island. It is a small species similar to T. scolopax Watson, 1882, from the Kerguelen Islands. The shell is chalky white, with 10-11 axial lamellae crossed by five spiral cords on the last whorl. Adult specimens of the new species are illustrated, described and compared with other living species of the same genus and of similar geographic distribution. Lectotypes of T. septus Watson, 1882, and T. declinans Watson, 1882, are here designated. Fil: Pastorino, Roberto Santiago Guido. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina